Beyond Clinical High-Risk State for Psychosis: The Network Structure of Multidimensional Psychosis Liability in Adolescents - Fonseca-Pedrero, Eduardo; Ortuño-Sierra, Javier; Inchausti, Felix; Rodríguez-Testal, Juan Francisco; Debbané, Martin (Frontiers in Psychiatry, 2020)
Objectives: The main goal of the present study was to analyze the network structure of schizotypy dimensions in a representative sample of adolescents from the general population. Moreover, the network structure between schizotypy, mental health difficulties, subjective well-being, bipolar-like experiences, suicide ideation and behaviour, psychotic-like experiences positive and negative affect, prosocial behaviour, and IQ was analyzed. Method: The study was conducted in a sample of 1,506 students selected by stratified random cluster sampling. The Oviedo Schizotypy Assessment Questionnaire, the Personal Wellbeing Index–School Children, the Paykel Suicide Scale, the Mood Disorder Questionnaire, the Strengths and Difficulties Questionnaire, the Prodromal Questionnaire–Brief, the Positive and Negative Affect Schedule for Children Shortened Version, and the Matrix Reasoning Test were used. Results: The estimated schizotypy network was interconnected. The most central nodes in terms of standardized Expected Influence (EI) were ‘unusual perceptual experiences’ and ‘paranoid ideation’. Predictability ranged from 8.7% (‘physical anhedonia’) to 52.7% (‘unusual perceptual experiences’). The average predictability was 36.27%, implying that substantial variability remained unexplained. For the multidimensional psychosis liability network predictability values ranged from 9% (estimated IQ) to 74.90% (‘psychotic-like experiences’). The average predictability was 43.46%. The results of the stability and accuracy analysis indicated that all networks were accurately estimated. Conclusions: The present paper points to the value of conceptualizing psychosis liability as a dynamic complex system of interacting cognitive, emotional, behavioral, and affective characteristics. In addition, provide new insights into the nature of the relationships between schizotypy, as index of psychosis liability, and the role played by risk and protective factors.